Mixed Mathematical Inventory Management Model for a Dual Channel Retail WarehouseEspañol (2023)
Adding a new sales channel creates new challenges in terms of inventory management due to the difference in order size and fulfillment times as well as the uncertainty in the demand of both channels. The objective is to design a mixed inventory management model composed of a joint replenishment model for the traditional retail channel and a continuous review model for the Online channel, both with stochastic demand, due to the difference they present in their operational management. A heuristic method was developed to solve the problem and for its validation numerical examples were evaluated where an 11% reduction was found in the cost of the dual channel warehouse inventory policy with the proposed model which seeks to represent an approximation of management such as joint replenishment at retailers.